2014
DOI: 10.5713/ajas.2014.14255
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maize Source and Complex Enzymes on Performance and Nutrient Utilization of Broilers

Abstract: The objective of this study was to investigate the effect of maize source and complex enzymes containing amylase, xylanase and protease on performance and nutrient utilization of broilers. The experiment was a 4×3 factorial design with diets containing four source maize samples (M1, M2, M3, and M4) and without or with two kinds of complex enzyme A (Axtra XAP) and B (Avizyme 1502). Nine hundred and sixty day old Arbor Acres broiler chicks were used in the trial (12 treatments with 8 replicate pens of 10 chicks)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
3
4
0
1
Order By: Relevance
“…Tang et al . [ 18 ] reported that supplementation of combination of enzymes (xylanase, amylase, and protease) significantly (p<0.05) improved apparent ileal digestibility of CP, which is in agreement with our results. Similarly, Zhang et al .…”
Section: Discussionsupporting
confidence: 92%
“…Tang et al . [ 18 ] reported that supplementation of combination of enzymes (xylanase, amylase, and protease) significantly (p<0.05) improved apparent ileal digestibility of CP, which is in agreement with our results. Similarly, Zhang et al .…”
Section: Discussionsupporting
confidence: 92%
“…He suggest that enzyme addition to balanced vegetarian maize-soya diets may result in significant financial gains. Similar results have also been reported in more recent studies; using a combination of amylase, xylanase and protease was reported to be effective in improving the growth profiles of broilers fed maize-soybean-rapeseed-cotton mixed diets [33] . The multy-enzyme used in the present study does also have arabinofuranosidases, which is known as debranching enzymes, are able to cleave arabinose from the backbone and enhance the efficacy of xylanases.…”
Section: Discussionsupporting
confidence: 89%
“…Multi-enzyme activity products have been used commercially in broiler diets for over 2 decades. Several studies have reported that a combination of X, A, and P improve broiler performance and nutrient digestibility in corn-based diets (Olukosi et al., 2007 ; Cowieson and Ravindran, 2008 ; Tang et al., 2014 ). Romero et al.…”
Section: Introductionmentioning
confidence: 99%